Juvenile hyaline fibromatosis - Kitano, Y... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
Juvenile hyaline fibromatosis is a rare congenital disease with characteristicclinical and histopathological features. Clinical symptoms develop early in life, ranging from one month ro four years of age. Tumors andnodules are most outstanding symptoms. Whitish papules, hyperthropy of the gingiva and flexural contracture of joints are the essential symptoms. X-ray extamination often reveals osteolytic or destructive bone lesions. Histopathology shows abundant deposition of hyaline substance in the tumor. Inmost cases, those main symptoms are not directly life-threatening, but ultimate prognosis is poor.
Keywords: Congenital; Contracture; Fibroma; Gingival hypertrophy; Hyalin; Joints; Neoplasms, fibrous tissue; Osteolysis